Sustainable intensification in drylands: What resilience and vulnerability can tell us - Robinson, Lance W.; Ericksen, Polly J.; Chesterman, Sabrina; Worden, J.S. (Elsevier, 2015)
• We apply concepts from vulnerability and resilience to sustainable intensification in drylands. • We challenge the predominant "security-versus-intensification hypothesis". • Some forms of intensification can increase vulnerability and are therefore unsustainable. • Agricultural intensity is not the inverse of extensivity. • Sustainable intensification intensifies the most extensive systems, as extensive systems .